Kemudahan Sistem E-Banking terhadap Masyarakat Mengakses Sistem Informasi Perbankan Syariah pada Bank Syariah Indonesia (BSI) - Ibnu Syawali Manurung; Melisa Ananda Putri Ritonga; Febi Alicia; Nurbaiti Sirait (Da'watuna: Journal of Communication and Islamic Broadcasting, 2023)
In the 4.0 era, as now, the developments that have occurred in all fields are languishing in the banking world, as it is now, where information can be accessed easily whenever and wherever we are, one example of advances in information technology provided by Islamic banking is e banking, is one of the facilities provided by e banking to customers. This study uses a descriptive qualitative research method that aims to explain and explain clearly about a problem or an event, because the researcher feels that the problem being studied requires a deeper understanding.This study aims to aim at drawing conclusions about the ease of accessing e-banking in the present which is very easy to access, this convenience is not understood by ordinary people which makes the development of e-banking in Indonesian Islamic banking a little late. Islamic banking parties that are lagging behind conventional banking parties who have optimized convenience services so that it is easier for ordinary people to access is one of the problems with delays for Islamic banking, especially in Islamic banking Keywords: convenience, information system, Islamic banking